2015
DOI: 10.1007/s00204-015-1453-5
|View full text |Cite|
|
Sign up to set email alerts
|

Diquat causes caspase-independent cell death in SH-SY5Y cells by production of ROS independently of mitochondria

Abstract: Evidence indicates that Parkinson’s disease (PD), in addition to having a genetic aetiology, has an environmental component that contributes to disease onset and progression. The exact nature of any environmental agent contributing to PD is unknown in most cases. Given its similarity to paraquat, an agrochemical removed from registration in the EU for its suspected potential to cause PD, we have investigated the in vitro capacity of the related herbicide Diquat to cause PD-like cell death. Diquat showed greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 76 publications
(75 reference statements)
2
31
0
Order By: Relevance
“…3). Western blot analysis failed to detect the levels of cleaved caspase 3, a finding that has been observed previously [13].
Fig.
…”
Section: Resultssupporting
confidence: 80%
“…3). Western blot analysis failed to detect the levels of cleaved caspase 3, a finding that has been observed previously [13].
Fig.
…”
Section: Resultssupporting
confidence: 80%
“…Previous studies reported that exposure to nM concentrations of rotenone for 24 hours was found to decrease SH-SY5Y cell viability to 50% when compared to untreated cells [29,30]. However, rotenone at higher concentrations were needed to effect cellular viability in our study model, similar to recent studies [31,32]. At lower concentrations, we could not observe any damage.…”
Section: Discussionsupporting
confidence: 89%
“…We also could not observe necroptosis in PQ-exposed SH-SY5Y cells (Fig. 2), in contrast to the case of diquat that is an herbicide structurally resembling PQ and has been shown to cause necroptosis of SH-SY5Y cells (Nisar et al, 2015). Therefore, the unique feature of necroptosis-and ferroptosis-independent necrosis caused by PQ on SH-SY5Y cells might represent a model in which to search for a novel mechanism of necrosis.…”
Section: Discussionmentioning
confidence: 67%
“…Although there is much literature showing that apoptosis is the main mode of SH-SY5Y cell death during exposure to these substances, recent studies have shown possible involvement of necroptosis and/or ferroptosis in cell death by diquat and MPP+ (Nisar et al, 2015;Ito et al, 2017). Oxidative cellular stress is the main cause of PQ toxicity (Suntres, 2002) and the generation of lipid peroxides has been implicated mostly in PQ cytotoxicity (McCormack et al, 2005).…”
Section: Discussionmentioning
confidence: 99%